The effect of bilingualism on obligatory components of auditory late responses in young adults: a cross-sectional study - Ali Hajimohammadi; Fatemeh Heidari (The Egyptian Journal of Otolaryngology)
Abstract Introduction Bilingualism significantly contributes to neuroplasticity in the brain, with research indicating enhanced auditory processing in bilingual individuals. Obligatory sensory components of the auditory late responses (ALRs) reflect primary and secondary auditory cortex activity, serving as an electrophysiological measure of auditory processing. This study aims to compare ALRs' obligatory components (P1-N1-P2) in bilingual (Turkish-Persian) and monolingual (Persian) young adults. Method This cross-sectional study analyzed ALRs in 28 monolingual and 28 bilingual participants aged 19 to 30 years, using a 70 dB nHL speech stimulus (/da/). ALRs were recorded monaurally with insert earphones. The study then compared the mean latency and amplitude of P1- N1- P2 complex in the right and left ear between two groups. Result The study revealed shorter latency for all three ALRs components in bilingual participants compared to monolinguals. This difference was statistically significant (P-value < 0.05) for N1 with right ear stimulation and P2 with right and left ear stimulations. No significant differences were found in the amplitude of P1-N1 and N1-P2 between the groups. Conclusion The significant reduction in N1 and P2 latency observed in bilingual subjects' ALRs likely results from neural plasticity. This may enhance neural transmission and accelerate speech sound processing in the respective cortical regions. These latency changes could serve as a cortical neural biomarker distinguishing monolinguals from bilinguals, highlighting the impact of bilingualism on auditory processing efficiency.